Reading from paper, computers, and tablets in the first grade: The role of comprehension monitoring - Elena Florit; Pietro De Carli; Antonio Rodà; Kate Cain; Lucia Mason (Computers and Education Open)
Recent meta-analyses indicate poorer comprehension when reading from computers or handheld devices compared to paper-based reading of informational texts. Meta-analyses also suggest that this screen inferiority effect may be linked to individual differences in metacognition. However, most paper vs. screen research to date has been conducted with university students. This study investigated whether the inferiority of screen-based reading from computers and handheld devices for informational texts is evident in beginner readers and related to comprehension monitoring skills. In a within-subjects design, first graders' (N = 58; Mage = 6.8 years) comprehension of main point, literal and inferential information was assessed using one narrative and one informational (i.e., descriptive) text read on paper, computer (laptop), and tablet. Comprehension monitoring was assessed through an inconsistency detection task. A standardized measure of reading comprehension was included as a control in the main analyses. Supplementary analyses controlling for word reading accuracy and medium preferences were also run. Linear mixed models showed superiority of main point comprehension for descriptive texts presented on tablets and inferential comprehension for narrative over descriptive texts, independent of medium. Results for literal comprehension were mixed. In addition, comprehension monitoring was related to main point and literal comprehension regardless of medium and had a greater effect on descriptive than narrative text comprehension at the inferential level. A screen inferiority effect was not detected in beginner readers' comprehension of texts from two digital mediums. Text comprehension was supported by metacognition, independent of medium.